Analysis of design and technological processes of hot recycling asphalt mixture at batch asphalt mixing plants - Martišius, Mindaugas; Sivilevičius, Henrikas (International Conference “Environmental Engineering”, 2020)
European Union members seek to establish the principles of a circular economy, which is based on the efficient use of raw materials and resources. This requirement will have an impact on business and in particular on the road construction sector. Hence the need to improve the asphalt mixing plant (AMP) mixing technology utilizing as much as possible reclaimed asphalt pavement (RAP) to produce asphalt mixtures (AM) for road construction. The resources used to produce new AM in the world are endless and becoming more expensive in a time scale. The multicycle reuse of RAP producing AM is a priority, when thinking about of economical recycling materials usage and the saving of resources. The design and development of RAP hot recycling in-plant technologies has been in progress for approximately half a century. In high-level-economy countries, AM production currently processes on average approx. 80% of the amount of RAP using innovative techniques on AMPs. Design of various AMP, their assessment on the flexible application of innovative techniques depending on the RAP processing method, are described in this paper. In this paper different recycling technologies in AMP and their advantages and disadvantages are reviewed. The research result indicates technical possibilities hot recycling in-plant in Baltic countries. Local authorities, research institutes, road construction and road design companies could use these results in the future.